Closed-Vessel Conductively Heated Digestion of Dry Dog Food for Spectrometric Determination of Essential Nutrients - Costa, Rayane Cristina Vieira [UNESP]; Santiago, João Victor Biagi [UNESP]; Ferreira, Edilene C. [UNESP]; Virgilio, Alex [UNESP]; Gomes Neto, José Anchieta [UNESP] (Brazilian Journal of Analytical Chemistry, 2024)
The closed-vessel conductively heated digestion system (CHDS) was evaluated to digest dry dog foods for further determination of K, Na, Cu, Fe, Mn, and Zn by high-resolution continuum source flame atomic absorption spectrometry (HR-CS FAAS). The CHDS method was optimized using a fractional factorial design with five variables (HNO3 concentration, H2 O2 volume, temperature, holding time, and pre-digestion time) at two levels. The accuracy of the CHDS procedure was checked by the analysis of reference materials from the National Institute of Standards and Technology (NIST SRM 1577b Bovine Liver and 2976 Mussel Tissue) and Brazilian Agricultural Research Corporation (Embrapa MR-E1002A Fish Food). Also, the digestion efficiencies were calculated from residual carbon contents (RCCs). The RCC and blank values in the CHDS digested samples were consistently low, which is suitable for determinations using ICP OES and ICP-MS techniques. For comparison, all samples were also digested by microwave-assisted digestion in closed vessels (MW-AD). Results for Na, K, Cu, Fe, Mn, and Zn determined in sample digests obtained by CHDS were not statistically different at a 95% confidence level from those observed for MW-AD. Limits of quantification (LOQ) calculated from digests in CHDS and MW-AD were comparable, and the values provided adequate limits for elemental determinations in dog foods. Data from mineral composition and moisture were employed in a clustering analysis (HCA) and the discrimination of the samples among different manufacturers and food for dogs at different life stages was possible.
Keywords: CHDS; dog food; HR-CS FAAS; pet nutrition; sample preparation